Cultural Creativity in the Early English Renaissance Popular Culture in Town and Country - Salter, E. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
This book is about the ways that ordinary people in town and country creatively define themselves, their families and their social networks. It explores inheritance strategies, personal possessions, attitudes to commemoration after death, the daily fashioning of identity and the interactions between imagination and daily life.